The Ipsilesional Upper Limb Can Be Affected following Stroke - Gemma H. Kitsos; Isobel J. Hubbard; Alex R. Kitsos; Mark W. Parsons (The Scientific World Journal)
Objective. Neurological dysfunction commonly occurs in the upper limb contralateral to the hemisphere of the brain in which stroke occurs; however, the impact of stroke on function of the ipsilesional upper limb is not well understood. This study aims to systematically review the literature relating to the function of the ipsilesional upper limb following stroke and answer the following research question: Is the ipsilesional upper limb affected by stroke? Data Source. A systematic review was carried out in Medline, Embase, and PubMed. Review Methods. All studies investigating the ipsilesional upper limb following stroke were included and analysed for important characteristics. Outcomes were extracted and summarised. Results. This review captured 27 articles that met the inclusion criteria. All studies provided evidence that the ipsilesional upper limb can be affected following stroke. Conclusion. These findings demonstrate that clinicians should consider ipsilesional upper limb deficits in rehabilitation and address this reduced functional capacity. Furthermore, the ipsilesional upper limb should not be used as a “control” measure of recovery for the contralateral upper limb.